STRATEGI KOMUNIKASI PT. TASPEN (PERSERO) MAKASSAR DALAM PROGRAM CORPORATE SOCIAL RESPONSIBILITY BINA LINGKUNGAN DI KECAMATAN PATTALASSANG KABUPATEN GOWA - Millenia Mulyadi , Deasy; Majid , Abd; Ahdan, Ahdan (UNIVERSITAS MUSLIM INDONESIA, 2022)
This study aims to determine the strategy of PT. Taspen (PERSERO) Makassar in determining & utilizing CSR programs for environmental development, namely in Patalassang District, Gowa Regency. This research method uses a descriptive qualitative approach, taking place at PT. Taspen (PERSERO) Makassar. Data collection techniques are observation, interviews and documentation. Miles & Huberman's interactive model analysis technique is to collect, reduce data, present data, and draw conclusions. The results of the study that the communication strategy in determining the CSR program at PT. Taspen (PERSERO) Makassar using the POAC (Planning, Organizing, Actuating and Controling) principles and looking at the resources available in the company, stakeholders (stakeholders) and seeing the needs of the community so that the budget issued is right on target. Communication strategy of PT. Taspen (PERSERO) Makassar in utilizing this CSR program, it can be seen that the 2 units ambulance assistance program distributed by PT. Taspen Makassar is able to provide great benefits to the community / improve the welfare of the people in Pattalassang so that the company has the opportunity to cooperate with other parties and improve social environmental sustainability with this CSR program, it can improve a positive image for the company